2013 22nd International Conference on Noise and Fluctuations (ICNF) 2013
DOI: 10.1109/icnf.2013.6578989
|View full text |Cite
|
Sign up to set email alerts
|

Noise characteristics of AlInN/GaN HEMTs at microwave frequencies

Abstract: The microwave noise parameters measured on AlInN/GaN HEMTs devices with different gate length values are presented in this paper. 0.15-µm HEMTs achieve a maximum current density of 700 mA/mm at V GS = 0 V and a measured extrinsic transconductance of 350 mS/mm. The current gain cutoff frequency and the maximum oscillation frequency are 40 GHz and 70 GHz, respectively. At 10 (20) GHz, the device exhibits a minimum noise figure of 0.8 dB (1.8) dB with an associated power gain of 14 (8.8) dB. Below 8 GHz, the gate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 20 publications
0
7
1
Order By: Relevance
“…Excellent microwave noise performance for AlGaN/GaN HEMTs on SiC [4]and Si substrates [5][6][7] have already been reported. Recently, few groups have also reported the microwave noise performances of InAlN/GaN HEMTs on SiC substrates [8][9][10]. At 10 GHz, Sun et al, reported a 0.1-µm-gate InAlN/GaN HEMT with NF min value of 0.62 dB but with an improved associated gain (G a ) of 15.4dB when compared to AlGaN/GaN HEMTs (G a =11.2dB) [6].…”
Section: Introductionmentioning
confidence: 99%
“…Excellent microwave noise performance for AlGaN/GaN HEMTs on SiC [4]and Si substrates [5][6][7] have already been reported. Recently, few groups have also reported the microwave noise performances of InAlN/GaN HEMTs on SiC substrates [8][9][10]. At 10 GHz, Sun et al, reported a 0.1-µm-gate InAlN/GaN HEMT with NF min value of 0.62 dB but with an improved associated gain (G a ) of 15.4dB when compared to AlGaN/GaN HEMTs (G a =11.2dB) [6].…”
Section: Introductionmentioning
confidence: 99%
“…Finally, the transmission line metal-stack Ti/Au (50/1000 nm) was formed and passivated with 420 nm-thick SiN by plasma enhance chemical vapour deposition. on SiC substrate [11]. Fig.…”
Section: Methodsmentioning
confidence: 99%
“…Another cause of high shot noise and thus higher noise figures of the device is due to the gate leakage as reported in [9][10][11]. To circumvent these adverse effects, we report a AlGaN/AlN/GaN HEMT on Si substrate with improved device structure design that enhances the microwave noise performance.…”
Section: Introductionmentioning
confidence: 99%
“…The value of NF min increases dramatically by about 0.05 dB when the value of V ds grows from 5 V to 6 V, as shown in Figure 17, and the increases in NF min with V ds are minimal for V ds >6 V. The changes in the carrier velocity in the channel cause the initial abrupt increase in NF min with V ds. 35 NF min rises due to a variety of causes, including an increase in I ds and power dissipation. 35 The carrier velocity reaches saturation when V ds rises over 5 V, and preconditioning variations in the carrier density are most likely to be responsible for the initial increase in NF min .…”
Section: Noise Modelling In Vertical Cavet Gan Mis-hemtsmentioning
confidence: 99%